NGL-1/LRRC4C Deletion Moderately Suppresses Hippocampal Excitatory Synapse Development and Function in an Input-Independent Manner - Choi, Yeonsoo; Park, Haram; Jung, Hwajin; Kweon, Hanseul; Kim, Seoyeong; Lee, Soo Yeon; Han, Hyemin; Cho, Yisul; Kim, Seyeon; Sim, Woong Seob; Kim, Jeongmin; Bae, Yongchul; et al. (Frontiers in Molecular Neuroscience, 2019)
Netrin-G ligand-1 (NGL-1), also known as LRRC4C, is a PSD-95–interacting postsynaptic adhesion molecule that interacts trans-synaptically with presynaptic netrin-G1. NGL-1 and its family member protein NGL-2 are thought to promote excitatory synapse development through largely non-overlapping neuronal pathways. While NGL-2 has been shown to be critical for excitatory synapse development in specific dendritic segments of neurons in an input-specific manner, whether NGL-1 has similar functions is unclear. Here, we show that NGL-1 deletion in male mice moderately suppresses excitatory synapse development and function, but surprisingly, does so in an input-independent manner. While NGL-1 is mainly detected in the stratum lacunosum moleculare (SLM) layer of the hippocampus relative to the stratum radiatum (SR) layer, NGL-1 deletion leads to decreases in dendritic spine density in both SLM and SR layers in the ventral hippocampus. In addition, both SLM and SR excitatory synapses display suppressed short-term synaptic plasticity in the ventral hippocampus. These morphological and functional changes are either absent or modest in the dorsal hippocampus. The input-independent synaptic changes induced by NGL-1 deletion involve abnormal translocation of NGL-2 from the SR to SLM layer. These results suggest that NGL-1 deletion moderately suppresses hippocampal excitatory synapse development and function in an input-independent manner.